Tren Sastra Eropa dan Keterpengaruhannya Terhadap Sastra Arab (Kajian Sastra Banding) - Angga Mustaka J.P (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
ABSTRACTTrends in European Literature and its influence on Arabic Literature, comparative literary studies. The background of this article departs from the many literary schools in Europe that have an influence on Arabic literature. The research method used is a qualitative method. The data collection technique used is the collection of documents or documentation. The data analysis technique in this article uses the Creswell model of qualitative data analysis. The approach used in this research is the historical approach. The results of this research are; 1) The literature that pioneered the birth of comparative literary studies, namely is French literature. 2) American literature emerged as a response to French literature. 3) The influence of European literature on Arabic literature can be seen from the characteristics of European poets who are very oriented to the rules and styles of Arabic literature. 4) The influence between European literature and Arabic literature was also caused by the many Arab writers who migrated to Europe for various reasons. Abstrak Artikel ini bertujuan untuk membahas tren Sastra Eropa serta keterpengaruhannya terhadap Sastra Arab, kajian sastra banding. Adapun latar belakang dari artikel ini berangkat dari banyaknya madzhab-madzhab sastra di Eropa yang mempunyai keterpengaruhan terhadap Sastra Arab. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan historis. Teknik pengumpulan data yang digunakan adalah pengumpulan dokumen atau dokumentasi. Teknik analisa data pada artikel ini menggunakan analisa data kualitatif model Creswell. Hasil penelitian ini adalah; 1) Sastra yang mempelopori lahirnya kajian sastra banding yaitu adalah sastra Perancis.2) Sastra Amerika muncul sebagai respon dari Sastra Perancis. 3) Keterpengaruhan Sastra Eropa terhadap Sastra Arab terlihat dari ciri khas para penyair Eropa yang sangat berorientasi pada kaidah-kaidah dan gaya Sastra Arab. 4) Keterpengaruhan antara Sastra Eropa dan Sastra Arab juga disebabkan akibat banyaknya sastrawan Arab yang hijrah ke Eropa dengan berbagai alasan